Analisis Pola Penyebaran Kemiskinan Kabupaten dan Kota se-Indonesia - Rosalinda (UNIVERSITAS LANCANG KUNING, 2021)
Poverty is one of the fundamental issues that has become a serious concern of the government. One of the most important thing to support the strategy of poverty reduction is providing of poverty data which is accurate and on target. BPS provides the data and information on poverty as well as indicators related to poverty issues at the district/city in Indonesia. The purpose of this research is to analyze the pattern of poverty distribution based on clustering the districts and cities in Indonesia and also revealing information based on the patterns formed. This research consisted of 12.072 data cells which is covering 503 districts/cities throughout Indonesia and 24 poverty indicators which is processed using factor analysis and cluster analysis. The results of this research are based on cluster analysis that three interesting clusters will be discussed which were formed the similarity patterns, namely : 1) Cluster I has 11 districts with a correlation of 75,7%, 2) Cluster II has 57 districts with a correlation of 75,5%, and 3) Cluster III has 55 cities with a correlation of 65,4%. Therefore, in formulating the policies, the local governments should notice to the characteristics of region poverty, so that the policies are suitable with the needs of their respective regions.